#### Answer

$x = \dfrac{-By+C}{A}$

#### Work Step by Step

Add $-By$ to both sides to find:
$Ax + By + (-By) = C + (-By)
\\Ax = -By + C$
Divide both sides by $A$ to find:
$\dfrac{Ax}{A} = \dfrac{-By+C}{A}
\\x = \dfrac{-By+C}{A}$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$x = \dfrac{-By+C}{A}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.